VALIDASI BUKU PENILAIAN BERBASIS LITERASI SAINS (BuPeNa BeRiSi) UNTUK CALON GURU SEKOLAH DASAR - Widiyanti, Ifa Seftia Rakhma; Mizan, Saeful (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2021)
The purpose of this study was to find a Assessment Book based Science Literacy with the specific aim of knowing the validity of it. This research was conducted at the PGRI Ronggolawe University Tuban (UNIROW) for students of PGSD UNIROW class 2019. The research period was started from April to August 2020. The research design used in this study was the Dick and Carey development model. This research design is used because it is more specific in its development. In the early stages of the research, research was carried out, namely the research stage or literature study to obtain information about the product needs to be developed. The development stages consist of seven stages, they were (1) needs analysis, (2) analysis of the form of BuPena BeRiSi, (3) analysis of the material with the skills to be achieved, (4) formulating goals for achieving skills, (5) developing BuPena BeRiSi , (6) BuPena BeRiSi validation, (7) BuPena BeRiSi revision. BuPena BeRiSi products have not been tested extensively because they have been hampered by the Covid-19 pandemic. The validation results show that the assessment of the content and language suitability components gets good criteria. The graphic components and the conformity of the technical requirements obtain excellent criteria. The component that got the highest percentage score was the graphic component with a score percentage of 91.67%. The suitability component of the technical requirements obtained a score of 90.63% with excellent criteria. The content and language suitability components obtained a score of 75% in the good category.